Akibat Hukum Perceraian Pada Perkawinan Campuran - I Wayan Ika Suyun Yastika; I Nyoman Putu Budiartha; Ni Made Pupspasutari Ujianti (Jurnal Analogi Hukum, 2019)
Besides choosing to vacation amid the beauty of the island of Bali, these tourists are sometimes also interested in the beauty of the women on the island of Bali to become partners and do mixed marriages. But in the midst of the large number of mixed marriages that exist in Bali and in the Badung Regency in particular, couples of different nationalities often separate in the middle of their life journey and do not know what effects of divorce on the mixed marriages they lead. From the background above, the author takes the title of the thesis "Legal Effects of Divorce in Mixed Marriage". The formulation of the problem in this study is how the filing of a mixed divorce lawsuit in the Badung religious court and how the legal impact on joint property, children's citizenship and child custody as a result of divorce in a mixed marriage. The type of research that I use in writing this essay is a type of empirical research. This type of research is guided by facts that exist in the community and from relevant people's information and is supported by applicable legislation so that it can explain the problems in more detail. The results of the study can be concluded that the property in mixed marriages among citizens is included in the field of personal status, so that if there is a divorce, the freedom to determine the law that applies to their marriage property is based on the law relating to the distribution of property, for a child's trust by the court, and regarding the status of citizens in the citizenship law it is stipulated that children of mixed marriages between citizens have 2 nationalities until the child is 18 years old.